Combretum micranthum G. Don – an African miracle of traditional herbal medicine - Barabasz-Krasny, Beata; Dobrzyński, Piotr; Sołtys-Lelek, Anna; Zandi, Peiman (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2025)
Combretum micranthum G. Don, a species also known as kinkéliba, is a plant widely used in traditional medicine in West Africa. Thanks to its richness in bioactive compounds such as flavonoids, tannins, and alkaloids, it exhibits a broad spectrum of medicinal properties – ranging from antiinflammatory and antioxidant effects to supporting digestion and regulating blood sugar levels. In folk medicine, it is used to treat among others fever, malaria, liver disorders, and infections. Due to the growing interest in natural therapies, C. micranthum is attracting the attention of researchers as a potential source of new plant-based drugs. This plant represents a fascinating example of the intersection between traditional knowledge and modern phytotherapeutic research.